Measuring and Reporting the 'Replacement' Cost of Oil and Gas Reserves (Book). - Manes, René P.; Burns, Thomas J. (The Accounting Review, 1978)
Abstract Reviews the book "Measuring and Reporting the 'Replacement' Cost of Oil and Gas Reserves," by Glenn A. Welsch and Edward B. Deakin.